ANALISIS KEBUTUHAN PELATIHAN BERBASIS DIGITAL UNTUK PENINGKATAN KOMPETENSI GURU PAI DALAM MENERAPKAN PRINSIP-PRINSIP KURIKULUM MERDEKA - Solihin (Fakultas Agama Islam, Universitas Mathla'ul Anwar, 2025)
This study aims to analyze the need for digital-based training for Islamic Education (PAI) teachers in order to enhance their professional competence in implementing the principles of the Kurikulum Merdeka at SMPIT Al Mumtaz. The focus of this research is directed toward mapping teachers’ digital competencies, identifying challenges in technology-based learning, and determining relevant training needs to support the implementation of differentiated learning and formative assessment. This research employs a qualitative descriptive approach designed to gain an in-depth understanding of the real context and conditions of PAI learning practices at SMPIT Al Mumtaz. Data were collected through several techniques, including in-depth interviews with PAI teachers, direct classroom observations, and analysis of learning documents and teaching materials used by the teachers. The findings reveal that the digital competence of PAI teachers remains at a basic to intermediate level, particularly in the use of digital evaluation applications and interactive learning media. Teachers also face difficulties in designing teaching modules and learning activities aligned with the principles of the Kurikulum Merdeka, especially regarding differentiated instruction and technology-based authentic assessment. The needs analysis indicates that teachers require comprehensive digital training, including mastery of technological tools, the design of digital teaching materials, and the development of technology-based pedagogical competence. This study emphasizes that structured, continuous, and needs-based digital training will significantly enhance PAI teachers’ ability to implement the Kurikulum Merdeka effectively at SMPIT Al Mumtaz.